Android phones for dummies - Gookin, Dan (Hoboken, NJ John Wiley & Sons, Inc, 2014)
From setup and configuration to taking advantage of the latest features, this guide helps you get the most out of your Android smartphone. Gookin walks you through the basics of making calls, sending e-mails and texts, making the most of Android apps, and more
Your own android. Have a little android ; Initial android duties ; The android tour ; Text to type, text to edit -- The phone part. It's a telephone ; More telephone things ; Leave your message at the tone -- Stay connected. The address book ; Text messaging mania ; E-mail this and that ; Out on the web ; Your digital social life ; Text, voice, and video chat -- Amazing phone feats. There's a map for that ; Pics and vids ; O sweet music! ; Apps various and sundry ; More apps -- Nuts and bolts. No wires, ever! ; Connect, store, share ; On the road again ; Customize and configure ; Maintenance, troubleshooting, and help -- The part of tens. Ten tips, tricks, and shortcuts ; Ten things to remember
Includes index
Previous edition: 2012
1 3
Keywords: Android (Electronic resource); Mobile computing; Smartphones